Principals’ Leadership, Parental Attachment, And Learning Motivation In Islamic Education: A Functionalist View - Ummi Qudsiyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Background: This study is grounded in the significance of school principals’ leadership quality in shaping students’ learning motivation, particularly in Islamic Education learning at the elementary school level. Aim: The main focus of this research is to analyze the influence of principal leadership quality on students’ learning motivation and to examine the mediating role of parental attachment in this relationship. Method: This study employed a mixed-method approach with a causal design. Data were collected through questionnaires distributed to 105 students from grades IV, V, and VI at SD Muhammadiyah Pahandut Palangka Raya, and were analyzed using SPSS and Hayes' PROCESS path analysis model (Model 4). Results and Dıscussion: The results showed that principal leadership quality had a significant influence on students’ learning motivation (B = 0.2275; p < 0.001), with parental attachment serving as a significant partial mediator (B = 0.1732; CI [0.1195, 0.2312]). These findings are supported by Talcott Parsons’ social functionalism theory, which views schools as social institutions that perform functions of adaptation, goal attainment, integration, and value maintenance. Conclusion: The study concludes that collaboration between school leadership and parental involvement is key to holistically enhancing students’ learning motivation.